Thermal performance analysis of PCM-integrated freezer systems using numerical simulation - Sena, Boni; Muhamad Faturrahman Al Hafizh; Muhammad Penta Helios; Muhammad Azril Rahmaditya; Rinaldi Suzatmiko; Dimas Bahrudin; Pratikara Herlambang; Ridwan Abdul Hakim; Nadia Amanah; Nurnida Elmira Othman (JTTM : Jurnal Terapan Teknik Mesin, 2026)
Improving temperature stability in household freezers is an important aspect of energy conservation in refrigeration systems. One approach is the integration of Phase Change Materials (PCM) as thermal energy storage media. This study aims to design and analyze the thermal performance of a PCM-integrated freezer system using cooking oil and paraffin wax as candidate PCM materials. The refrigeration system was designed using R290 refrigerant and analyzed using CoolTools software for vapor compression cycle simulation and ANSYS Student for transient thermal simulation based on the Finite Element Method (FEM). The thermodynamic analysis produced an actual COP of 2.94 from the CoolTools simulation and a calculated thermodynamic COP of 3.27, indicating acceptable refrigeration performance under low-temperature operating conditions. The transient thermal simulation results showed that paraffin wax did not exhibit a distinct temperature plateau during the transient heating process, indicating that latent heat effects were not dominant within the simulated operating temperature range. Cooking oil demonstrated a faster thermal response due to its relatively higher effective thermal conductivity, whereas paraffin wax provided better temperature stabilization and delayed heat transfer behaviour. The results demonstrate that the thermophysical properties of PCM significantly influence heat transfer characteristics and temperature distribution inside the freezer compartment. Therefore, selecting PCM materials with appropriate latent heat capacity and thermal conductivity is essential for improving temperature stability and reducing temperature fluctuations in refrigeration systems.